Orange Fleshed Sweetpotato is here to stay in Angola - International Potato Center (2013)
Women farmers of Ukuma in Huambo Province process orange-fleshed sweetpotato (OFSP) roots to make bread, juice, and cakes for their families. They are very conscious about the high nutritional value of OFSP, especially for vitamin A. Improved sweetpotato varieties produced yields three times higher than existing local varieties, and were sold in the market, augmenting farmers’ income.